ETIKA PEMERINTAHAN BERBASIS MORALITAS KRISTEN DAN NASIONALISME: IMPLEMENTASI TEOLOGI POLITIK CALVIN DALAM KERANGKA SOEKARNO - Timotius, Timotius (Moriah Theological Seminary, 2025)
This study explores the synergy between Christian morality, especially in the political theology of John Calvin, and Soekarno's nationalism in building governmental ethics in Indonesia. Christian morality in Calvin's political thought strongly emphasizes the values of integrity, honesty, accountability, love, and justice—values that are particularly relevant for addressing issues of corruption, abuse of power, and social inequality. Meanwhile, Soekarnoism prioritizes inclusive nationalism, the spirit of mutual cooperation (gotong royong), and national unity to advance the people's welfare. The author employs a qualitative approach through a literature review to examine the possibility of merging these two value systems to establish governance that is ethical, fair, and centered on people. The results show that this synergy can strengthen the principles of justice, public service, sustainable development, and responsible resource management, especially within the framework of Indonesia's pluralism. This analysis highlights the significance of cooperation among religions, cultures, and institutions in fostering a political culture that is healthy, transparent, and fair.. In the Indonesian context, this collaboration includes Christian values according to Calvin, Soekarno's nationally oriented nationalism, as well as Islamic morality which emphasizes trust (responsibility), ‘adl (justice), and ukhuwah (brotherhood). Thus, this study not only connects the ideas of two figures but also integrates them within the framework of national pluralism. Penelitian ini mengeksplorasi sinergi antara moralitas Kristen terkhusus dalam teologi politik John Calvin, dan nasionalisme Soekarno dalam membangun etika pemerintahan di Indonesia. Moralitas Kristen dalam konsep politik Calvin sangat menekankan nilai-nilai integritas, kejujuran, akuntabilitas, kasih, dan keadilan yang relevan untuk menangani masalah korupsi, penyalahgunaan kekuasaan, dan ketimpangan sosial. Sementara itu, Soekarnoisme mengedepankan nasionalisme inklusif, semangat gotong royong, dan kesatuan bangsa untuk memajukan kesejahteraan rakyat. Penelitian ini menerapkan metode kualitatif, di mana penulis akan meneliti potensi penggabungan kedua kerangka nilai ini untuk menciptakan pengelolaan pemerintahan yang etis, adil, dan berfokus pada kesejahteraan masyarakat. Hasilnya mengindikasikan bahwa kolaborasi ini dapat memperkuat prinsip keadilan, pelayanan publik, pembangunan berkelanjutan, dan manajemen sumber daya yang bertanggung jawab, terutama dalam konteks pluralisme di Indonesia.. Studi ini menegaskan pentingnya kolaborasi lintas agama, budaya, dan institusi untuk membangun budaya politik yang sehat, transparan, dan berkeadilan. Dalam konteks Indonesia, kolaborasi ini mencakup nilai-nilai Kristiani menurut Calvin, nasionalisme Soekarno yang bercorak kebangsaan, serta moralitas Islam yang menekankan amanah (tanggung jawab), ‘adl (keadilan), dan ukhuwah (persaudaraan). Dengan demikian, penelitian ini tidak hanya menghubungkan pemikiran dua tokoh, tetapi juga mengintegrasikannya dalam kerangka pluralisme bangsa.